Amplified fragments length polymorphism (AFLP) analysis of markers associated with H5 and H22 Hessian fly resistance genes in bread wheat - Boukhatem N.; El-Jaafari S.; Najimi B.; Jlibene M.; Paul R.; Jacquemin J.M. (Biotechnologie, Agronomie, Société et Environnement, 2002)
Hessian fly, Mayetiola destructor (Say), is one of the most destructive pest of wheat (Triticum species) worldwide. In Morocco, damage caused by Hessian fly can result in total crop loss if high infestations occur during early stages of crop development. Genes that confer resistance to Hessian fly provide the most efficient and economical means of crop protection against this damaging insect. To date, 27 resistance genes (HJ-H27) have been reported in wheat; among these, 11 are very effective in Morocco. In this study, we have utilized amplified fragment length polymorphism (AFLP) analysis in conjunction with near-isogenic lines (NILs) and bulked segregant analysis (BSA) to identify molecular markers linked to Hessian fly resistance genes in bread wheat. Two pairs of NILs were used as source of DNA, one differing for H5 resistance gene and the other for H22 resistance gene. Using 42 primers combinations, 4200 selectively DNA fragments were analyzed throughout the wheat genome, with an average of 100 bands per combination and per pair of NILs. This technique appeared to be promising, since 28 polymorphic bands were detected, among which 13 associated to H5 locus and 15 to H22 locus.